The High Achievers’ Learning Strategies And Experiences In Learning English - Baso Jabu; Asriati Asriati (Seminar Nasional LP2M UNM, 2021)
Abstrak. This study aims to explore the language learning strategy and language learning experience by the high achiever students in the English Department of UNM. The study employed interview, observation, and questionnaire using blended technique, online and offline. There are 3 respondents from English education students contribute to this study. The results suggest that the students used direct and indirect strategies interchangeably with emphasized on the indirect one. All respondents are exposed to English since early ages. Since then, they actively involved in English competition and English society. Kata Kunci: Learning Strategy, Learning Experience, High Achiever Students